2020
DOI: 10.1039/d0ra07026b
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the enhanced photocatalytic activity of Mo and P codoped SrTiO3from first-principles prediction

Abstract: In this study, the synergistic effect of cation codoping (Mo and the cation P) on the band structure of SrTiO3 is demonstrated to enhance its photocatalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…11,22,25−27 Previous theoretical works demonstrate that the structure with X binding to M was more stable than that with X far away from M in (X + M)-doped semiconductors. 31,46,47 In Y 2 Ti 2 O 7 , an acceptor level induced by substituting an N 3− dopant for an O 2− site can be compensated by a donor level generated by substituting an M 5+ dopant for a Ti 4+ site or substituting an M 4+ dopant for a Y 3+ site. In a similar way, two acceptor levels induced by substituting a C 4− dopant for an O 2− site can be compensated by two donor levels generated by substituting an M 6+ dopant for a Ti 4+ site or substituting an M 5+ dopant for a Y 3+ site.…”
Section: Computational Detailsmentioning
confidence: 99%
“…11,22,25−27 Previous theoretical works demonstrate that the structure with X binding to M was more stable than that with X far away from M in (X + M)-doped semiconductors. 31,46,47 In Y 2 Ti 2 O 7 , an acceptor level induced by substituting an N 3− dopant for an O 2− site can be compensated by a donor level generated by substituting an M 5+ dopant for a Ti 4+ site or substituting an M 4+ dopant for a Y 3+ site. In a similar way, two acceptor levels induced by substituting a C 4− dopant for an O 2− site can be compensated by two donor levels generated by substituting an M 6+ dopant for a Ti 4+ site or substituting an M 5+ dopant for a Y 3+ site.…”
Section: Computational Detailsmentioning
confidence: 99%
“…We constructed a 2 × 2 × 2 supercell, consisting of 40 atoms, to investigate the effects of rare earth element co-doping and the microscopic influence of doping concentration on the structural phase and electronic structure of CaTiO 3 (see Figure 1). As the majority of perovskite materials employ this model structure in their calculations to maintain precision [8,47,51], our choice of this model enhances the reasonableness and reliability of our subsequent calculations. Moreover, the doping effect was initiated at different positions during co-doping by replacing oxygen atoms proximally and distally (1-proximally and 2-disrally), depending on the position of doped rare earth elements.…”
Section: Crystal Structure and Formation Energymentioning
confidence: 99%
“…In this regard, the CaTiO 3 (CTO) perovskite has gained considerable attention for its broad photocatalytic properties, including its ability to degrade organic pollutants and reduce carbon dioxide emissions in an environmentally friendly manner [5][6][7]. However, pure CaTiO 3 exhibits only moderate photocatalytic activity for hydrogen evolution due to its large band gap (~3.5 eV), which is only capable of using part of ultraviolet light, accounting for only 5% of solar energy [8]. On the one hand, the choice of preparation methods [9], including solid-state, co-precipitation, mechanochemical, sol-gel, hydrothermal and solvothermal process, significantly impacts the properties of perovskite materials Among these methods, hydrothermal routes for CaTiO 3 have gained prominence due to their ability to produce well-crystallized nanoparticles with customizable shape and size at relatively low processing temperatures [10].…”
Section: Introductionmentioning
confidence: 99%
“…So, we only consider the structure with X dopant in the subsurface layer in the following discussion. Previous DFT calculations revealed that in (X+M)-doped semiconductors, the model with X near to M was energetically more favorable than that with X far away from M. [68][69][70] For (X+M)-doped La 2 Ti 2 O 7 , we have constructed and optimized structures with X adjacent to M and with the distance of about 6 Å between X and M dopants, respectively. The calculated formation energies indicate that the configuration with X binding to M is more stable than the one with X far away from M by 0.66 eV for (N+V), 0.36 eV for (N+Nb), 0.22 eV for (N+Ta), 0.59 eV for (N+Mo), 0.75 eV for (N+W), 2.42 eV for (C+Mo), and 1.69 eV for (C+W).…”
Section: Formation Energy Of Co-doped Systemsmentioning
confidence: 99%